Fatty acids and elemental composition as biomarkers of Octopus vulgaris populations: Does origin matter?. (February 2019) - Arechavala-Lopez, P.; Capó, X.; Oliver-Codorniú, M.; Sillero-Rios, J.; Busquets-Cortés, C.; Sanchez-Jerez, P.; Sureda, A.
Abstract: The present study describes the novel use of fatty acids (FAs) and element profiles of Octopus vulgaris inhabiting three coastal areas in the W-Mediterranean Sea. These populations are exposed to different anthropogenic activities, and were compared at different geographical scales. The FA composition in the mantle of O. vulgaris exhibited significant differences in 22:6 n−3 (DHA) and 22:5 n−3 (EPA) among the sampled populations. The essential microelements Fe, Cu, Zn and Ni, and the non-essential microelements As, Sr, Al and Cd were the main contributors of variability among sampled octopus populations, with some notable differences among tissues. The variations in the FAs and elemental composition in octopus tissues were detected with other populations throughout the species distribution range, which might reflect differences in natural habitats and foraging strategies. Therefore, these may be considered biomarkers as a proxy to distinguish the origin of octopus specimens at different scales. Highlights: Fatty acid profiles of octopus mantles were similar among octopus populations. Significant differences were detected in DHA and EPA levels among octopus populations. Among tissues, digestive glands showed the highest variation in elemental composition. Non-essential elements (metals) differed significantly among octopus populations. Fatty acids and elemental composition might be biomarkers of octopus origins.